Krāsu pētījuma tēma vizuālās mākslas stundās 8. klasē - Bistrjakova, Tatjana (Latvijas Universitāte, 2007)
Šajā diplomdarbā ir izpētītas krāsu nokrāsas un krāsu gammas dabā un iespēja šo tēmu apgūt 8.klasē vizuālās mākslas stundās. Tā struktūru veido ievads, pamattēmas izklāsta piecas nodaļas, nobeigums, anotācijas, izmantotās literatūras un avotu saraksts, pielikumi. Pirmajā nodaļā izpētīti franču ainavistu K.Monē un P.Sezana atstāti mantojumi. Otrajā nodaļā pētīti latviešu mākslinieku ainavistu darbi. Trešajā nodaļā tika pētīta tēma, kā pareizi fotografēt ainavas. Ceturtajā nodaļā aprakstīta mācību uzdevumu kopas izstrāde, mācību programmas apraksts, mācību metodes, 8.klasesskolēnu vecumposma īpatnības. Piektajā nodaļā aprakstītas stundas, veltītas diplomdarba tēmai. Veikta izpildīto uzdevumu vērtēšana un rezultātu analīze.

The present diploma paper investigates the shades of colours in the nature and possible ways of teaching the given topic during the Art lessons in class 8. The present paper consists of introduction, five parts, conclusion, annotation, list of literature and sources, appendices. The first part of the diploma paper investigates art of French landscapists K.Monet and P.Cezanne. The second part investigates paintings of Latvian artists-landscapists. The third part shows how to take pictures of landscapes. The fourth part works out tasks, teaching programme, teaching methods, as well as investigates teenagers’ age group peculiarities. The fifth part contains lesson plans, principles of evaluation and results of the given tasks. The introduction of the given topic gave learners the possibility to work creatively and acquire the shades of colours in the nature. The obtained experience can help in further teaching process. The appendix of the present diploma paper contains reproductions of famous painters, learners’ pictures, lesson plans, and evaluation principles. The author of the diploma paper has come to a conclusion that the cooperation between the learners and teacher is an important factor of the teenagers’ development.
The theme of colour study at visual art lessons in Grade 8
Keywords: Pedagoģija